Whole issue - Language Value (Universitat Jaume I. Department of English Studies, 2019)
Table of Contents From the editors Mari Carmen Campoy-Cubillo Nuria Edo Marzá Articles  Audiovisual materials: A way to reinforce listening skills in primary school teacher education. Pilar González-Vera Ana Hornero Corisco Discourse markers and lecture structure: their role in listening Comprehension and EMI lecturer training. María Ángeles Martín del Pozo Multimodal digital tools and EFL audio-visual comprehension: Students' attitudes towards vodcasts. Natalia Norte Fernández-Pacheco Book and Multimedia Reviews  Arsenio Jesús Moya Guijarro. A Multimodal Analysis of Picture Books for Children: A Systemic Functional Approach. Frances Litzler